Efektivitas Video Pembelajaran Pola Gerak Tobi-Komi pada Kata Heian Godan untuk Meningkatkan Keterampilan Karateka Pemula - Chaerul Alam; Abdul Rachman Syam Tuasikal; Heryanto Nur Muhammad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to examine the effect of video-based learning media on improving Heian Godan kata skills among beginner karateka. The study employed a quantitative approach using an experimental method with a pretest–posttest control group design. A total of 30 beginner karateka participated in this study and were divided into an experimental group and a control group. The experimental group received video-based learning media, while the control group was trained using conventional methods. The research instrument was an assessment sheet for Heian Godan kata skills. Data were analyzed using normality tests, homogeneity tests, paired sample t-tests, and independent sample t-tests. The results indicated that both groups showed significant improvements in kata skills (p < 0.05); however, the experimental group demonstrated a greater improvement than the control group. The independent sample t-test revealed a significant difference between the two groups (p < 0.05). It can be concluded that video-based learning media have a significant effect on improving Heian Godan kata skills among beginner karateka. Therefore, video-based learning media are recommended as an alternative or complementary approach to conventional karate training methods. Keywords: Karate, Heian Godan Kata, Motor Skills, Video-Based Learning Media